Rural Tourism: a comparative analyses from Galicia and North of Portugal - José Cadima Ribeiro; Laurentina Cruz Vareiro; Carmen Padin Fabeiro; Xulio Pardellas de Blas (European Regional Science Association (ERSA), 2004)
This paper unveils the results stemming from two parallel researches, whose scope of analysis was tourism in rural areas (TRA) structures, as established in both northeast regions of the Iberia Peninsula which shape the Euro-region Galicia-North of Portugal. Firstly, a descriptive analysis of the regulations and the TRA supply for both territories is presented, and an evaluation of the strategies which have been followed by the private entrepreneurs and the public administration of each of them, as far as the utilisation of resources is concerned, is done. The symmetries and asymmetries of the touristic structures of those regions are also underlined. In the second part of this study, the above mentioned strategies will be discussed at length seeking to pinpoint how they configure and shape very similar touristic models based upon the use of natural and historical resources, which somehow display common features. Finally, it is sought to materialise a brief conclusion. Key Words: Tourism in Rural Areas (TRA), touristic strategies, TRA models
Keywords: 330; Tourism in Rural Areas (TRA); touristic strategies; TRA models